Empowering Student Learning Outcomes Through Problem-Based Learning in Social Science - Kasmi Aryuli; Armiati Armiati (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2023)
The purpose of this investigation was to examine the impact of the problem-based learning (PBL) approach on the learning outcomes of seventh-grade students in the subject of Social Science. The study employed a quasi-experimental design and targeted all seventh-grade students at SMPN 03 Batang Anai Padang Pariaman. Purposive sampling was utilized to select two classes, utilizing class VII.4 as the experimental group and class VII.5 as the control group, each containing 32 students. The PBL model was employed in the experimental group through instructional videos, while direct observation assignments were used in the control group. The findings demonstrated that the PBL model significantly enhanced the learning outcomes of students in the experimental group, thereby validating the effectiveness of this approach in enhancing the learning outcomes of students.